UTILIZAÇÃO DE EMBALAGENS ATIVAS Á BASE DE PECTINA EM CARNE DE FRANGO - DORNAS, Isabeli Mantovani; GOMES, Ana Carolina Alves; DALEGRAVE, Caroline de Brito; MADALOZZO, Elisângela Serenato; SANTOS, Aylpy Renan Dutra; OLIVEIRA, Dalton Mendes (ANAIS DO ENIC, 2026)
.